2019
DOI: 10.1038/s41598-019-40915-w
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4/PF4 is a predictive biomarker of cardiac differentiation potential of human induced pluripotent stem cells

Abstract: Selection of human induced pluripotent stem cell (hiPSC) lines with high cardiac differentiation potential is important for regenerative therapy and drug screening. We aimed to identify biomarkers for predicting cardiac differentiation potential of hiPSC lines by comparing the gene expression profiles of six undifferentiated hiPSC lines with different cardiac differentiation capabilities. We used three platforms of gene expression analysis, namely, cap analysis of gene expression (CAGE), mRNA array, and microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Further, our enrichment analysis showed downregulation of a number of genes, viz. Pf4, Gdf6, Sall1, Apln, Kctd11, and Twist2 have functions associated with the differentiation of cardiomyocytes, endothelial cells and striated muscles (66,69,(73)(74)(75)(76). In addition to differentiation, the regulation of proliferation in cardiomyocytes is important for heart development and its normal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Further, our enrichment analysis showed downregulation of a number of genes, viz. Pf4, Gdf6, Sall1, Apln, Kctd11, and Twist2 have functions associated with the differentiation of cardiomyocytes, endothelial cells and striated muscles (66,69,(73)(74)(75)(76). In addition to differentiation, the regulation of proliferation in cardiomyocytes is important for heart development and its normal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 46 ] reported a generation of 80 to 95% cTnT + cells in 2D for an embryonic stem cell line (HuES6) and three different hiPSC lines (FS3.2, PF6.2, and SPF5.2). The differences in yield might be due to the unknown—and possible later—timepoint of flow cytometry analyses by these authors, or the different stem cell lines used, which are known to frequently affect general hiPSC differentiation outcomes [ 67 , 68 ]. For example, Zhang et al [ 46 ] observed beating generally after 6 days, while iPS11 cells started beating after 7–8 days in culture ( Figure 4 ), a dissimilarity that could be attributed to line or handling differences.…”
Section: Resultsmentioning
confidence: 99%
“…This protein is chemotactic for numerous other cell type and also functions as an inhibitor of hematopoiesis, angiogenesis and T-cell function. It is involved in regulating the differentiation of hematopoietic stem cells/progenitor cells, maintaining the survival and self-renewal of hematopoietic stem cells, and regulating the cardiac differentiation potential of induced pluripotent stem cells ( 32 , 33 ). Previous studies have shown that PF4 is an endocrine factor, and its overexpression in tumors is associated with decreased OS of patients ( 34 ).…”
Section: Discussionmentioning
confidence: 99%